Towards the implementation of performance information procurement system in the Nigerian construction industry - Buba, Simon Peter Gumgaro (2019)
A majority of the procurement of projects in Nigeria are faced with the lack of transparency, accountability and corruption in contract awards and execution. These have been well documented in literature. Besides, the existing traditional procurement model has not been able to address issues of non-performance in the Nigerian construction industry (NCI) related to cost, time, quality and client’s satisfaction. Based on a review of relevant literature, it has been ascertained that the Best Value Procurement / Performance Information Procurement System (BVP/PIPS) is the best system to minimise risk of non-performance, increase transparency, accountability and add value to projects through the use of expertise thereby, improving project delivery. Hence, this research developed a framework for PIPS implementation in the NCI to guide professionals in addressing non-performance in the industry. Thus, a deductive research using quantitative research approach was adopted. Data related to existing weaknesses in the Nigerian procurement system, association of the traditional procurement approach to project performance, factors that can hinder PIPS implementation in Nigeria, PIPS unique success factors and existing factors that can aid in implementing PIPS in Nigeria were collected using a survey questionnaire. The survey was administered to 314 construction professionals. Consequently, the data were analysed using descriptive and inferential statistics. The results showed that the traditional procurement approach did have an association with project performance, and construction professionals did agree that both PIPS unique factors and existing factors can help improve project delivery in the NCI. The results were confirmed through the use of Partial Least Squared Structural Equation Modelling (PLS-SEM) using SmartPLS3 software. Based on the findings, a PIPS implementation framework to improve project performance in Nigeria was developed and this was validated by expert opinion through an online questionnaire which revealed that the framework can guide the implementation of PIPS in the NCI to improve project delivery.